Phenotypic characterization of Coffea arabica genotypes in infested area by nematode Meloidogyne paranaensis - Carvalho, Alex Mendonça; Salgado, Sonia Lima; Mendes, Antonio Nazareno; Pereira, Antonio Alves; Botelho, Cesar Elias; Tassone, Guilherme Augusto; Lima, Renato Ribeiro (Coffee Science - ISSN 1984-3909, 2017)
The Meloidogyne paranaensis causes serious damage to the root system of coffee; it could cause poor vegetative and reproductive development culminating in the death of plants. This trial was carried out aimed to evaluate, in naturally infested by M. paranaensis, vegetative growth, production in the first two years (2011/2012) and the population of the M. paranaensis in genotypes (GEN) Timor Hybrid UFV 408-01 pl.1 R1 GEN 5); Sarchimor pl.1 R1 (GEN 34); the Catuai Vermelho crossings x Amphillo 2161 pl.1 R1 (GEN 15); Catuai Vermelho x Amphillo x 2161 pl.3 R1 (GEN 21); Catuai Vermelho x Amphillo 2474 pl.1 R2 (GEN 22) and as standard cultivars IPR 100, Catuaí Amarelo IAC 62 and Mundo Novo 379-19. M. paranaensis population (eggs + juveniles seconds estádio.g-1 of root), production in the first two years, vegetative vigor, crown diameter, plant height and grain size, were evaluated. In area infested by M. paranaensis, GEN 15 (Catuai Red x Amphillo 2161 pl.1 R1) was the most similar to IPR 100 in assessed agronomic characteristics; GEN 21 features yield high, and population high M. paranaensis, indicating the nematode tolerance behavior, and the GEN 34 is susceptible to nematode M. paranaensis.